PERENCANAAN PELAKSANAAN PROYEK KONSTRUKSI PADA PROYEK PEMBANGUNAN RUMAH SUSUN SEKOLAH TINGGI AGAMA HINDU NEGERI MPU KUTURAN SINGARAJA - I Gusti Ngurah Wiryadharma Verdianata; Ni Komang Armaeni; Ni Made Widya Pratiwi (Jurnal Teknik Gradien, 2023)
Project planning is the first step in managing the resources, funds and time that has been determined to complete the project. The project for the construction of the Mpu Kuturan Singaraja State Hindu Religious High School Flat is a project that has been implemented but does not have an existing plan yet. Therefore, the author tries to make a plan according to the method that has been studied. This plan consists of a Construction Project Implementation Method Plan, a Project Implementation Schedule Plan using the Precedence Diagram Method (PDM), an Implementation Cost Plan (RBP), a Cost Budget Plan (RAB), and a Achievement Schedule with the S Curve Method.